Inclusive pedagogy across the curriculum - Deppeler, Joanne, 1951- (Bingley, U.K. : Emerald, 2015)
This volume focuses on an inclusive pedagogical approach for enhancing teaching and learning in key areas of curriculum including: literacy, mathematics, science, social studies, and the arts. In the introductory chapters, the concept of inclusive pedagogy is framed in relation to the actions of teachers in providing quality teaching and learning experiences for everyone in inclusive classrooms. Unlike much of what has previously occurred in inclusive practice the approach does not differentiate by providing alternative teaching and learning for students who are different. Focusing on what is to be learned in a particular subject area, the intention is to avoid the issues associated with defining some learners as different.
Teaching and learning for all / Joanne Deppeler, Tim Loreman, Ron Smith -- Conceptualising inclusive pedagogy : the inclusive pedagogical approach in action / Lani Florian -- Strengthening literacy and numeracy in early childhood / Joseph Seyram Agbenyega -- Literacy learning : designing and enacting inclusive pedagogical practices in classrooms / Annette Woods, Barbara Comber, Radha Iyer -- Effective and inclusive mathematics teaching and learning / Helen Forgasz, Jill Cheeseman -- The role of values in teaching and learning science / Deborah Corrigan, Kathy Smith -- Inclusive pedagogy in physical education / Gerald Griggs, Richard Medcalf -- Enhancing inclusion in geography classrooms / Michael Phillips, Stephen Cranby -- Music: naturally inclusive, potentially exclusive? / Jennie Henley -- Using inclusive pedagogy in visual arts : engagement with 'the masters' / Andrea Daly -- Tablets, tweets and talking text : the role of technology in inclusive pedagogy / Donna R. McGhie-Richmond, Catriona de Bruin -- Meaning-making, language learning and language using : an integrated approach / Do Coyle -- Cross-curriculum design : enacting inclusive pedagogy and curriculum / Julianne Moss, Kate Harvie -- Teaching for quality learning : a focus on inclusive pedagogy / John Loughran.
Print version record
Keywords: Education -- Special Education -- General; Teaching of specific groups & persons with special educational needs; Inclusive education